Enforcement of maintenance order in the Melaka Syariah Court / Aliyah Abdullah, Salmiah Salleh and Nasreen Miza Hilmy Nasrijal (Institute of Research, Development and Commercialization (IRDC), 2007)
When a claimant obtains an order from the Court, in particular an order awarding them maintenance, most claimants are under the impression that it is the court's duty to ensure that the defendant pays. Unfortunately, in some situations, a claimant does not get what is awarded to her and her children because the defendants (ex-husbands) do not pay. Unknown to some claimants, it is in fact their duty to proceed with the enforcement of the maintenance order to get paid. This research, therefore, is designed to identify the obstacles in enforcing the maintenance order of the Syariah Court and to suggest possibilities to overcome the problems in enforcing the said order. The data for this research is sourced from personal interview with the Chief Registrar of the Melaka Syariah Court. Thereafter, questionnaires were designed based on the said interview and distributed to all the 29 Syarie lawyers who are in active practice in Melaka. It was found that the main obstacle in enforcing the maintenance order is the negative attitudes of the parties. The study also revealed that the whereabouts of the ex-husband is crucial in determining whether the maintenance order could be enforced because all modes of executing the order would require information of the ex-husband's whereabouts. Among the recommendations made in this study are to amend certain laws and to revamp the current education syllabus to instill positive attitudes.